Art and activism in the age of systemic crisis aesthetic resilience - Steinbock, Eliza 1980-; Ieven, Bram; Valck, Marijke de 1975- (Routledge, Taylor & Francis Group, 2021)
Resilience : searching for new weapons while fleeing -- Global conjunctions of aesthetic resilience -- Artistic practices of embodied resilience
Includes bibliographical references and index
2011
Keywords: Geschichte 1960-1980; Aktivismus; Kunstsoziologie; Arts / Political aspects; Art and social action; Konferenzschrift -- 2017 -- Leiden